Two Species of Passiflora (Passifloraceae) New to Nepal - Manandhar, Vidya; Kurmi, P. P. (Journal of Natural History Museum, 2009)
The present paper includes Passiflora ciliata Ait. & P. foetida L. as new records to flowering plants of Nepal. The description along with phytogeographical distribution and a key to facilitate the identification of species have been provided herewith. Key words: Distribution; flowering plants; Nepal; Passiflora ciliata; phytogeography Journal of Natural History Museum Vol. 23, 2008 Page 16-18